The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.cmi.2017.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Is antimicrobial stewardship cost-effective? A narrative review of the evidence

Abstract: AIMS: This narrative review aimed to collate recent evidence on the cost-effectiveness and cost-benefit of antimicrobial stewardship (AMS) programmes, to address the question 'is AMS cost-effective?', while providing resources and guidance for future research in this area. SOURCES: PubMed was searched for studies assessing the cost-effectiveness, cost-utility or cost-benefit of AMS interventions in humans, published from January 2000 to March 2017, with no setting inclusion/exclusion criteria specified. Refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 26 publications
0
35
0
4
Order By: Relevance
“…They recommend using behavioural sciences to select the most promising interventions, based on a careful assessment of barriers and facilitators. As a useful complement, Naylor et al reviewed the cost-effectiveness of antimicrobial stewardship programmes [6]. Having found few studies in the literature, they make recommendations for future research.…”
mentioning
confidence: 99%
“…They recommend using behavioural sciences to select the most promising interventions, based on a careful assessment of barriers and facilitators. As a useful complement, Naylor et al reviewed the cost-effectiveness of antimicrobial stewardship programmes [6]. Having found few studies in the literature, they make recommendations for future research.…”
mentioning
confidence: 99%
“…Regarding the outcome elements, in countries that lack data and resources, the value of ASPs is not always reported with metrics that allow for program assessment ( 33 ). Recently published reviews ( 34 36 ) showed that cost-effectiveness studies are most common in the United States and European countries. In fact, a recent review ( 34 ) showed that only one study of cost-effectiveness had been developed in LMICs.…”
Section: Discussionmentioning
confidence: 99%
“…This inventory was then refined through an iterative process, including a series of team virtual discussions and emails about its appropriateness. Data from 441 textual sources were then independently and systematically mapped and coded along three dimensions: a. type -mandatory requirements, recommendations, or national campaigns; b. method -restrictive, persuasive, and/or structural in nature [27], [28]; c. level of implementation -macro (national), meso (organisational), and/or micro (individual) levels. This was done independently and concurrently between the research teams.…”
Section: (Ii) Assessment Of the Health Policy Settingmentioning
confidence: 99%